2008
DOI: 10.2478/v10040-008-0057-z
|View full text |Cite
|
Sign up to set email alerts
|

Flame Spread in Cable Tray Fires and its Modeling in Fire Simulation Codes

Abstract: Abstract. A vertical cable routing on different trays has been observed as worst case in case of fire. PVC (polyvinyl chloride) or FRNC (fire retardant non-corrosive) polymers have been used as cable insulation materials for cables typically being installed in German NPP. Each experiment has been repeated under pre-heated conditions. A propane gas burner has been used for igniting cables and an ethanol pool for pre-heating. Two different types of fire simulation codes (one 'lumped parameter' code -COCOSYS -and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Different strategies have been developed to model the fire development in cable tray installations. Performance of several computational fluid dynamics (CFD) codes, to estimate fire development and propagation in cable tray installations, have been compared in the past [20]. Based on Cone Calorimeter data from the FIPEC project mathematical models for material pyrolysis were created [21].…”
Section: Introductionmentioning
confidence: 99%
“…Different strategies have been developed to model the fire development in cable tray installations. Performance of several computational fluid dynamics (CFD) codes, to estimate fire development and propagation in cable tray installations, have been compared in the past [20]. Based on Cone Calorimeter data from the FIPEC project mathematical models for material pyrolysis were created [21].…”
Section: Introductionmentioning
confidence: 99%
“…It is stated in Askit et al that the configuration of cables “may play a role as significant as physical and chemical properties on the cable response to fires.” Furthermore, the influence of “loading, bundling, grouping and spacing of cables” on the extent of flame spread, and thus, the severity of the fire, has been highlighted in the context of the FIPEC (Fire Performance of Electric Cables) project . Very often, a cable tray is represented as a single rectangular slab that defines the material surface where the fuel undergoes a pyrolysis process before being burned. However, such an approach does not allow reproducing a realistic flame pattern.…”
Section: Introductionmentioning
confidence: 99%
“…This would not be the case if each tray were modeled as one homogeneous rectangular slab (see Figure ). One way to account for the space between cables when they are not densely packed is to model longitudinal slots of air between the cables, as suggested in Röwekamp et al It is important also to mention that, in the approach presented herein, thermal degradation of the cables (ie, pyrolysis), which is a very complex process, is not modeled. Instead, flame spread is predicted based on a surface ignition approach where the heat up and ignition are modeled, but the burning rate is prescribed.…”
Section: Introductionmentioning
confidence: 99%
“…Considering this complexity and the developmental state of flame spread models, it was recommended to resort to heat release rates derived from tests conducted with a similar configuration, favoring the development of an experimental database. Predicting the heat release rate of cable tray fires is still qualified as highly complex in a more recent work . Later on, among the PRISME 2 program, a benchmark exercise was performed, aimed at assessing the ability of fire modeling to predict a cable tray fire in confined and ventilated compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Predicting the heat release rate of cable tray fires is still qualified as highly complex in a more recent work. 12 Later on, among the PRISME 2 program, a benchmark exercise was performed, aimed at assessing the ability of fire modeling to predict a cable tray fire in confined and ventilated compartments. It was concluded that simulating cable fires in confined conditions is very complex by contrast with liquid fuel fire simulations that have a higher level of maturity.…”
mentioning
confidence: 99%